Xylanase Activity of Streptomyces violascences BF 3.10 on Xylan Corncobs and its Xylooligosaccharide Production - Wida Salupi; . Yopi; A. Meryandini (Faculty of Animal Science, Bogor Agricultural University, 2015)
Corn is one of the important carbohydrate sources in Indonesia that is mainly used for food and industrial materials. In addition, the byproducts of corn, such as corncobs, have been reported as xylan-containing materials that can be utilized as substrate in xylooligosaccharides (XOS) production. XOS are natural prebiotic fibers that can enhance the performance of animal’s digestive system. The main objective of this study was to exploit xylan from corncobs to produce XOS. The research consisted of extraction and production of xylan from corncobs and the synthesis of XOS from corncob-produced xylan. The corncob and Streptomyces violascens BF 3.10 xylanase is a collection of PPSHB IPB Laboratory. Corncobs xylan extracted by using alkaline method and reducting sugar was analyzed by dinitrosalicylic acid method. The xylan extraction from corncobs could produce 7.93% (w/w) of xylan. The activity of S. violascens BF 3.10 xylanase on the substrate of concorb-produced xylan was 6.4 U/mL at the optimum temperature of 60 °C in 50 mM phosphate buffer with pH 5.5. The thin layer chromatography analysis indicated that 1% (w/v) corn-cob xylan could produce XOS with degree of polymerization (DP) 3.92. XOS, with DP ranging from 2-4, could be used as a livestock feed mixture to stimulate the growth of normal microbes in the gastrointestinal tract of livestock.Key words: corncobs, Streptomyces violascens BF 3.10, xylan, xylanase